TOURISM PROMOTION AND SERVICES STRATEGIES TO INCREASE THE NUMBER OF VISITORS DURING THE COVID-19 PANDEMIC - Fadliyani Nawir; Nur Alam; Titus Indrajaya; Indra Kusumawati (International Journal of Economy, Education and Entrepreneurship, 2022)
This research is research for qualitative reasons (field research). They are collecting data using the method of observation, interviews, questionnaires and documentation. Respondents who were sampled in this study were 42 people. At the same time, the analysis uses qualitative descriptive analysis. The study results indicate that the manager carries out the promotion and service strategy by increasing the number of visitors by implementing a promotional mix, namely advertising through electronic media and social media. Promotion by holding events and entertainment. Advertising using newspapers and electronic media. Meanwhile, in the implementation of TERRA, it is tangible by providing the necessary installations. Empathy by serving friendly current visitors, reliability with clear service standards and management expertise, responsible responsiveness, reactivity to function quickly and respond, and assurance by providing guarantees for visitors